The Diversity of Anti-Microbial Secondary Metabolites Produced by Fungal Endophytes: An Interdisciplinary Perspective - Mousa, Walaa K.; Raizada, Manish N. (Frontiers in Microbiology, 2013)
Endophytes are microbes that inhabit host plants without causing disease and are reported to be reservoirs of metabolites that combat microbes and other pathogens. Here we review diverse classes of secondary metabolites, focusing on anti-microbial compounds, synthesized by fungal endophytes including terpenoids, alkaloids, phenylpropanoids, aliphatic compounds, polyketides and peptides from the interdisciplinary perspectives of biochemistry, genetics, fungal biology, host plant biology, human and plant pathology. Several trends were apparent. First, host plants are often investigated for endophytes when there is prior indigenous knowledge concerning human medicinal uses (e.g. Chinese herbs). However, within their native ecosystems, and where investigated, endophytes were shown to produce compounds that target pathogens of the host plant. In a few examples, both fungal endophytes and their hosts were reported to produce the same compounds. Terpenoids and polyketides are the most purified anti-microbial secondary metabolites from endophytes, while flavonoids and lignans are rare. Examples are provided where fungal genes encoding anti-microbial compounds are clustered on chromosomes. As different genera of fungi can produce the same metabolite, genetic clustering may facilitate sharing of anti-microbial secondary metabolites between fungi. We discuss gaps in the literature and how more interdisciplinary research may lead to new opportunities to develop bio-based commercial products to combat global crop and human pathogens.